Critical velocity of continuous and intermittent running exercise. An example of the limits of the critical power concept - Kachouri, M.; Vandewalle, H.; Billat, V.; Huet, M.; Thomaidis, M.; Jousselin, E.; Monod, H. (European Journal of Applied Physiology, 1996)
The relationship between exhaustion time (tlim) and distance Dlim for running exercises at constant velocity until exhaustion can be described by a linear relationship (Dlim = a + b tlim) whose slope corresponds to a critical velocity. Seven runners participated to the study which compared the critical velocity of continuous versus intermittent running exercises. The critical velocity for continuous running (Vcritc) was calculated from the results (tlimc and Dlimc) of running exercises performed at 95 and 105% of the final velocity of the Montreal Track Test (vMTT). The intermittent running consisted of repetitions of running exercises performed at 95 and 105% vMTT during a time equal to half the value of the corresponding tlimc. The subjects recovered during a time equal to running time while jogging at a slow pace. The critical velocity for intermittent running (Vcriti) was calculated from the cumulated running distance (Dlimi) and cumulated running time (tlimi) corresponding to 95 and 105% vMTT. Vcriti was equal to Vcritc (4.56 +/- 0.444 m.s-1 vs 4.60 +/- 0.416 m.s-1). Nevertheless, in some subjects, the repetition numbers were very different for the intermittent running exercises at 95 and 105% vMTT. This paradoxical result could be explained by the fact that the value of Vcrit should be theoretically little sensitive to a large error in the value of tlim corresponding to a velocity slightly higher than critical velocity, for intermittent exercises as well as continuous exercises.